BUSINESS ETHICS FOR BUSINESS SUSTAINABILITY IN MUHAMMADIYAH HOSPITAL: EVIDENCE FROM PONOROGO, INDONESIA - Anna Marina; Sentot Imam Wahjono (Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
The purpose of this study is to examine how business ethics can support business sustainability in hospitals. Business ethics is associated with: Hospital professional ethics, medical professional ethics, professional accounting ethics, and Islamic business ethics. This study used a qualitative approach with phenomenological analysis techniques to process the data collected from key informants, through Focus Group Discussions (FGD) with 20 supervisors, in-depth interviews with six members of the management, 11 outside observations, and documentation over a period of six months. The business ethics theory was used to guide the research’s findings. The business sustainability theory was used to find the relationship of the research’s findings with the opinions of four expert informants for the purpose of triangulation on the reasons for conducting Islamic business ethics for a sustainable business. The finding of this study is the reason for running the hospital ethically. The finding of this study can be used to redesign the vision and mission of the hospital as a basis for achieving better performance. The implication of the finding of this research is the need for business ethics in the design of internal systems.